A case of endogenous endophthalmitis complicated by neutropenia following bacteremia with Streptococcus mitis resistant to beta-lactam antibiotics. (February 2013) - Ono, Yuichiro
Abstract This report is focused on a case of endogenous endophthalmitis following Streptococcus mitis bacteremia that occurred during chemotherapy for acute myeloid leukemia, despite broad-spectrum beta-lactam antibiotics and vancomycin. The patient partially recovered visual acuity. In conclusion, Streptococcus mitis bacteremia complicated by febrile neutropenia may cause endogenous endophthalmitis within a very short timeframe.